Evaluation of Research Opportunities and Limitations for Plastic Surgery Residents: An International Survey. Issue 5 (November 2021) - Navia, Alfonso; Berner, Juan Enrique; Ramirez, Joaquin; Will, Patrick; Tejos, Rodrigo; Dagnino, Bruno; Searle, Susana; Cuadra, Alvaro
Abstract : Supplemental digital content is available in the text. Abstract : Background: Conducting research during specialty training provides an opportunity to develop critical thinking and leadership skills along with a better understanding of the scientific literature. However, trainees often find it difficult to undertake research, in the context of labor-intensive surgical training. The aim of this study is to evaluate the research output and limitations of plastic surgery residents in different countries. Methods: An international cross-sectional study involving plastic surgery trainees and recent postgraduates from Brazil, Chile, Germany, and the United Kingdom was conducted. A survey inquiring into academic productivity, limitations to conducting research, and working-hours patterns was distributed among eligible participants. Results: From September to December 2019, 106 surveys were retrieved. Most respondents declared having participated in at least 1 project that resulted in a presentation or publication during their training (90.6% in national presentations, 68% international presentations, 67% in national publications, and 66% international publications). Having completed a previous research fellowship was associated with a statistically higher academic output ( P < 0.05). Seventy-nine percent of respondents felt that their participation in research activities would have been greater if limiting factors had been addressed, including lack of time (72.5%) and insufficient supervision and mentoring (55%). Conclusions: Optimizing plastic surgery trainees' participation in scientific research is beneficial both for residents and their mentors. Research fellowships can provide an opportunity for academically oriented trainees to further develop their research skills. Protected time and adequate mentoring can help not only to increase residents' research output, but also to recruit the next generation of academic plastic surgeons.